Implementasi Electronic-Know Your Customer pada aplikasi Fintech untuk meningkatkan keamanan akun user - Putra, Diego Belva; Hakim, M. Abd. Malik; Nurdewanto, Bambang (Universitas Merdeka Malang, 2023)
The information technology development can make financial transactions easier, but the security of Fintech applications such as Bangbeli is a critical issue that can be addressed through the implementation of the Electronic-Know Your Customer (E-KYC) feature to increase user trust. The aim of this research is to apply E-KYC technology as an additional feature in the Bangbeli application at PT. Doa Anak Digital. The approach used is the agile development method which consists of six stages, including requirements, design, development, testing, implementation and review. This research uses a qualitative approach, involving interviews with selected sources to ensure that the E-KYC feature can improve user account security. Implementation includes coding and implementing E-KYC in the Bangbeli application, followed by testing using the black box method to identify errors or bugs in the E-KYC system. The results of the research show conformity with the initial design, with features that run according to their function. As a result of interviews with users and Bangbeli regarding the implementation of the E-KYC feature, a number of feedback were obtained including an easy to understand flow, innovations that increase security, confidence in sending personal data, and the impression that this platform cares about user security.